Evaluation of burn wound healing property of ocimum sanctum by monitoring of period of re-epithelization in rabbits - Gupta, Vaibhav K.; Pathak, Swanand S.; Jain, Mahesh K. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Burns remain a major public health problem all over the world, especially in developing countries. Pseudomonas aeruginosa is a major cause of infection and a contributing factor in the death of patients with burns. So, there is a growing need to develop drugs which will prevent infections and complications more effectively than the presently used drugs. Ocimum sanctum L. (Tulsi in Hindi) has been shown to have antioxidant properties, which may be responsible and favorable for faster wound healing. The present study was carried out to evaluate the wound healing property of O. sanctum by monitoring the period of re-epithelization in thermal burns with and without supportive treatment of ointment silver sulfadiazine. Methods: Wound healing property of O. sanctum was evaluated by monitoring the period of re-epithelization. Results: The period of re-epithelization, in Control group was 34 ± 1.26 days, in Standard group treated with ointment silver sulfadiazine was 30.33 ± 1.37 days, in group treated with O. sanctum was 30.50 ± 1.87 days and in group treated with ointment silver sulfadiazine + O. sanctum was 26 ± 1.41 days. Conclusions: Group treated with ointment silver sulfadiazine + O. sanctum showed minimum re-epithelization period. So, the most effective treatment for burn wound healing in this study was ointment silver sulfadiazine + O. sanctum.